2011
DOI: 10.17348/era.9.0.181-215
|View full text |Cite
|
Sign up to set email alerts
|

Surviving on Knowledge: Ethnobotany of Chepang community from mid-hills of Nepal

Abstract: The Chepangs of Nepal are rich in knowledge regarding the use of different plants and this knowledge has been transferred verbally through the generations. This study analyzed traditional knowledge regarding plant use among the Chepang communities from ward number 3 and 4 of Shaktikhor Village Development Committee located in the central mid hills of Nepal. Semi-structured interviews were conducted with key informants like traditional healers for medicinal plants, and elder people and women for edible and othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 13 publications
0
32
0
Order By: Relevance
“…An ethno-botanical study in the same area indicated that a total of 434 species are used by the Chepangs and out of these 362 are wild species (Rijal, 2011). This clearly indicates that significantly more species are found in the forest than enumerated in this study.…”
Section: Diversitymentioning
confidence: 49%
See 2 more Smart Citations
“…An ethno-botanical study in the same area indicated that a total of 434 species are used by the Chepangs and out of these 362 are wild species (Rijal, 2011). This clearly indicates that significantly more species are found in the forest than enumerated in this study.…”
Section: Diversitymentioning
confidence: 49%
“…1) were selected for this study. The study area falls in Mahabharat hills which are inhabited by the highly forest-dependent (Rijal, 2011) ethnic group called Chepang. Many publications mention that the forest resource base has decreased as a result of their extraction of forest products (Gurung, 1994;Bhattarai, 1995;SNV/SECOW, 1995) but, so far, these statements have not been supported by quantitative evidence.…”
Section: Study Areamentioning
confidence: 99%
See 1 more Smart Citation
“…A number of uncultivated plants having medicinal values have been used by the people in the region. Nontimber forest products in general and medicinal plants in particular are principle source of household health care of many rural households of the region (Adnan et al, 2012;Rijal, 2011;Shinwari, 2010;Thapa, 2009;Manandhar, 2002). Local people living in these areas since generations have been using these plant species through their indigenous knowledge to cure various diseases.They know the preparation of raw drugs from herbs through personal experience and ancestral prescription.…”
Section: Household Level Health Carementioning
confidence: 99%
“…Documentation of their indigenous knowledge through the ethnobiological approach may be significant to lead the discovery of drugs or to contribute for the economic development of local as well as nation 5 . In Nepal, a number of ethnobiological studies have been conducted 6,7,8,9,10,11,12,13 but many parts of the country remain unexplored.…”
Section: Introductionmentioning
confidence: 99%